Quinoa protein hydrolysates: antioxidant properties and cytoprotection against D-galactose-induced oxidative stress - Yang, Cheng; Yang, Chao; Zhou, Yuanyuan; Ma, Jibing; Wei, Yuming; Huang, Jie (Frontiers in Nutrition, 2026)
Quinoa is widely recognized as a high-quality protein source suitable for producing bioactive hydrolysates with significant health-promoting potential. This study compared four proteases (alcalase, trypsin, pepsin, and neutral protease) to identify optimal enzymatic conditions for generating antioxidant quinoa protein hydrolysates (QPHs). Among them, alcalase exhibited the highest degree of hydrolysis (36.15%) and yielded the largest proportion of low-molecular-weight fragments (< 2 kDa, 41.08%). It also produced hydrolysates with the lowest surface hydrophobicity and particle size, reflecting more extensive structural disruption, and demonstrated the highest essential amino acid content (20.72 g/100 g). Functionally, alcalase-derived QPHs showed the strongest DPPH radical scavenging activity (4.30 mg TE/g), the highest reducing power (0.61), and provided the greatest cytoprotection in HepG2 cells (83.43%), significantly enhancing SOD, GPx, and CAT activities while reducing MDA levels by 57.8%. Pepsin hydrolysate exhibited selective enhancement, showing the highest ABTS radical scavenging capacity (7.22 mg TE/g) and the greatest FRAP value (13.26 μmol TE/100 g DW), likely attributable to aromatic-rich fragments generated according to its cleavage specificity. Overall, these findings demonstrate that enzymatically derived QPHs, particularly those produced by alcalase, possess strong antioxidant activity and represent promising natural antioxidant ingredients for functional foods and nutraceutical formulations. The results also offer novel mechanistic insights supporting their application in health-promoting food products.